1950
DOI: 10.1001/jama.1950.02920050013003
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred Per Cent Oxygen in the Treatment of Acute Myocardial Infarction and Severe Angina Pectoris

Abstract: oxygen therapy in circulatory failure. When this disorder arises as a result of acute myocardial infarction, the administration of oxygen may relieve dyspnea, cyanosis and cardiac pain and tide the patient over the initial crucial stages of the attack. The diminution in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1955
1955
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Three studies reported benefit with oxygen therapy in pacing-induced angina43 and exercise-induced angina,44 45 although similar benefits could not be demonstrated in later studies 46 47. The other study was that of Madias et al ,48 who suggested that the administration of oxygen therapy to patients experiencing a MI may reduce ischaemic injury, based on precordial ST-segment mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported benefit with oxygen therapy in pacing-induced angina43 and exercise-induced angina,44 45 although similar benefits could not be demonstrated in later studies 46 47. The other study was that of Madias et al ,48 who suggested that the administration of oxygen therapy to patients experiencing a MI may reduce ischaemic injury, based on precordial ST-segment mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed recent debate in the cardiology literature has challenged the long established practice of administering 100% oxygen to acute angina and myocardial infarction (MI). Yet the first caution that administering 100% oxygen may be detrimental to ischemic myocardium in the normoxic patient was issued as long ago as 1950 [32]. In 1969 Bourassa et al [33] reported from experimental studies that high flow oxygen can reduce coronary blood flow sufficiently to worsen outcomes.…”
Section: The Danger Of Oxygen During Emergency Therapymentioning
confidence: 99%
“…In 1939 Riseman et al demonstrated that oxygen increased the workload that could be achieved before the development of angina in 11 of 17 patients[4]. However in1950 Russek et al reported that in 4 of 5 patients, oxygen resulted in either more pronounced or longer ECG manifestations of myocardial ischaemia during exercise compared to room air[20]. In 1961 Pons et al reported a reduction in ST segment depression during exercise with oxygen treatment in 8 of 10 patients[2].…”
mentioning
confidence: 99%